NEW APPROACH TO STRONG EARTHQUAKE PREDICTION IN THE SOUTH BAIKAL REGION ON THE BASIS OF ROCK DEFORMATION MONITORING DATA: METHODOLOGY AND RESULTS - S. A. Bornyakov; A. I. Miroshnichenko; G. V. Vstovsky; A. E. Sintsov; D. V. Salko (Геодинамика и тектонофизика, 2022)
The Southern Baikal is located within the actively developing Baikal rift zone (BRZ) that is characterized by a significant seismic potential, and M>7 earthquakes occur periodically with intensive shaking in the epicenters (up to 10 units). The problem of prediction and forecasting of strong earthquakes has always been critical for this region, considering its increasing urbanization, industrial clusters and transport systems. The article describes the methodology based on rock deformation monitoring data, which aims at developing a technology capable of efficient prediction and forecasting of strong earthquakes. In the Institute of Earth’s Crust SB RAS a set of studies is carried out in order to solve this problem, including those associated with the instrumental study of current movements of the lithosphere through GPS geodesy and deformations of rocks by strain gauges. The existing GPS sites and deformation measurements are combined into the Large-Scale Research Facilities "South Baikal instrumental complex for monitoring hazardous geodynamic processes" in frame of the Shared Research Facilities "Geodynamics and Geochronology" at the Institute of the Earth’s Crust, Siberian Branch of the Russian Academy of Science.In this article, the deformation monitoring methodology is described in application to the monitoring sites installed in the study area. The description includes the details of its conceptual basis, technical support and data processing methods. The discussion focuses on the instrumental measurements of rock deformation related to three strong events in the study area – Kultuk (August 27, 2008), Bystrinskoe (September 21, 2020), and Kudara (December 10, 2020) earthquakes. The features of the deformation process before these seismic events are given special attention with account of the structural-geodynamic settings and positions of local monitoring sites relative to the earthquake epicenters.